The Word Made Speculative? John Milbank's Christological Poetics - Bauerschmidt, Frederick Christian (Modern theology, 1999)
John Milbank's The Word Made Strange serves to answer many of the points raised by critics of his earlier Theology and Social Theory, in particular by developing more fully a "Trinitarian metaphysics" that take seriously the "poetic" character of human making and knowing. However, this metaphysics raises further questions regarding the underdevelopment of Milbank's Christology, Ecclesiology and Ethics. Specifically, Milbank's thin account of Jesus and the Church indicates an aversion to particularity that risks making his theology "merely speculative", and lessens its impact on concrete Christian communities.